(untitled) (Italian Journal of Public Health, 2010)
Background: Exposure to bioaerosols may pose health risks to workers operating in the processing of Urban Solid Waste (USW). The aim of this study is to evaluate microbiological air quality within an USW selection facility. Methods: Nine sampling points in an USW selection plant situated in central-southern Italy were selected. One outdoor sampling point provided the background data. Sampling was performed on a yearly basis (2005 – 2009) upon request by the management of the selection plant. Total Mesophilic Counts (TMC), as well as fungal and Gram-negative concentrations were determined. Results: The highest viable fungal particles concentrations (medians) were found in waste delivery areas (about 20000 CFU/m3), while the lowest were found in the control rooms (485 – 967 CFU/m3). TMC (median) was highest (6116 CFU/m3) at the delivery pit, followed by the machine shop (3147 CFU/m3), where no waste processing takes place. Medians of Gram-negative bacteria are below the suggested Occupational Exposure Limit of 1000 CFU/m3, although this limit was exceeded at several single time-points in the waste delivery areas, and also in a personnel resting room. The lowest Gram-negative contamination was found in the control rooms (medians <1 CFU/m3). Conclusions: Some areas within a USW selection plant act as internal sources of contamination towards those areas where partially processed waste, or no waste at all, is present. Well-designed air flows, or carefully- thought positioning of areas that are not directly involved in waste processing are necessary and effective in obtaining satisfactory microbiological air quality, provided that personal protection practices are strictly enforced.